The self-organising of youth volunteers during the Rena oil spill in New Zealand. Issue 1 (2nd January 2016) - Lockwood, Sarah; Weaver, C Kay; Munshi, Debashish; Simpson, Mary
ABSTRACT: This study explores the communication and organising of youth volunteers during a crisis, focusing on how they conceived, framed, and executed self-organising efforts during the 2011 Rena oil spill in New Zealand. It offers insights into the intersections of self-organising, youth volunteering and crisis events which have not been researched before. The study addresses two core research questions: 1. how was 'volunteering' conceptualised by youth volunteers involved in the Rena crisis; and 2. how did these volunteers communicate and self-organise during this crisis? The findings indicate that self-organising emerged out of a resistance towards structured responses and as a reaction to the inability of the official volunteer response to meet the needs of the community. Self-organised efforts were particularly attractive among youth volunteers because they offered flexibility, required minimal administrative processes, and fostered an environment of innovation and creativity. The volunteers' youthful energy and technological aptitude additionally drove their self-organised responses. The study identifies the considerable challenges that crisis officials faced in utilising youth volunteers despite the significant advantages of self-organising.